Study On The Interaction Of Zn(Ii) Ion With Metronidazole Drug In Aqueous Medium Using Electrochemical Techniques (Journal of the Asiatic Society of Bangladesh, Science, 2015)
This study includes the investigation of redox behavior of Zn2+ ion and its electrochemical nature when interacts with pharmaceutical drugs metronidazole. This research was carried out using cyclic voltammetry (CV), chronoamperometric (CA) and chronocoulometric (CC) techniques. The redox process of the Zn ion system in presence and in absence of metronidazole is diffusion controlled as well as adsorption controlled. This fact is supported by both CA and CC. The redox process of Zn ion system is quasireversible but almost irreversible in presence of metronidazole. pH change affects the redox behavior sharply and maximum interaction accurse at pH%.Asiat. Soc. Bangladesh, Sci. 41(2): 193-201, December 2015